Citation Patterns in Chemistry Dissertations at a Mid-sized University: An Internal Citation Analysis and External Comparison. Issue 2 (3rd April 2022) - Rose-Wiles, Lisa
ABSTRACT: This study analyzes the references cited in 34 chemistry dissertations and compares the results with an earlier study of citations in American Chemical Society journals. The dissertations cite more references and older references and a greater diversity of sources. They have the same tendency to heavily cite journal articles from a small core of traditional journals. This study underscores the value of comparing internal citation analyses with external citation analyses, and of analyzing the number of citing authors as well as the number of citations. Interlibrary loan and internal usage statistics were also used to inform collection development and library instruction.